3D‐Printed Periodic Hierarchical Porous rGO/Ti3C2Tx Architectures Induced Uniform Lithium Deposition for Li Metal Anodes. Issue 1 (6th October 2022) - Shi, Haiting; Pei, Mengfan; Wang, Shuo; Yao, Fengting; Xia, Yuanhua; Xu, Zhiwei; Liu, Shengkai; Shao, Ruiqi; Wang, Wei; Liang, Shuaitong
Abstract: Nonuniform Li + flux and lithiophilic sites cause uneven lithium deposition, which impedes the application of lithium metal batteries. Herein, a reduced graphene oxide (rGO)/Ti3 C2 Tx lattice with periodic printed holes is fabricated by 3D printing. Mesoporous structures formed by regularly assembled nanosheets provide abundant lithiophilic sites. The Li + flux is regulated by the periodic printed holes prepared by 3D printing. The deposition of lithium is homogenized by the synergistic effect of uniform Li + flux and abundant lithiophilic sites. The resultant 3D‐printed Li anode has excellent cycling stability up to 3000 h and a high average Coulombic efficiency of 98% after a long lifespan of ≈1000 h. Our work highlights the effect of the correlation between macroscopic and microscopic pores formed by 3D printing on inhibiting lithium dendrites, providing a novel pathway for highly 3D‐printed stable lithium metal anode. Abstract : This paper prepares a periodic 3D‐printed pores lattice to regulate Li + flux and guide even Li deposition. A structure with alternating layers of MXene and graphene constructs to eliminate the self‐restacking of single‐component nanosheets. The coupling effect of macroscopic and microscopic pores formed by 3D printing effectively suppresses lithium dendrites.